Albumin-driven disassembly of lipidic nanoparticles: the specific case of the squalene-adenosine nanodrug. Issue 4 (21st January 2020) - Gobeaux, Frédéric; Bizeau, Joëlle; Samson, Firmin; Marichal, Laurent; Grillo, Isabelle; Wien, Frank; Yesylevsky, Semen O.; Ramseyer, Christophe; Rouquette, Marie; Lepêtre-Mouelhi, Sinda; Desmaële, Didier; Couvreur, Patrick; et al.
Abstract : Albumin forms a complex with the squalene-adenosine prodrug and by doing so drives the disassembly of the squalene-adenosine nanoparticles. Abstract : In the field of nanomedicine, nanostructured nanoparticles (NPs) made of self-assembling prodrugs emerged in the recent years with promising properties. In particular, squalene-based drug nanoparticles have already shown their efficiency through in vivo experiments. However, a complete pattern of their stability and interactions in the blood stream is still lacking. In this work we assess the behavior of squalene-adenosine (SQAd) nanoparticles – whose neuroprotective effect has already been demonstrated in murine models – in the presence of fetal bovine serum (FBS) and of bovine serum albumin (BSA), the main protein of blood plasma. Extensive physicochemical characterizations were performed using Small Angle Neutron Scattering (SANS), cryogenic transmission electron microscopy (Cryo-TEM), circular dichroism (CD), steady-state fluorescence spectroscopy (SSFS) and isothermal titration calorimetry (ITC) as well as in silico by means of ensemble docking simulations with human serum albumin (HSA). Significant changes in the colloidal stability of the nanoparticles in the presence of serum albumin were observed. SANS, CD and SSFS analyses demonstrated an interaction between SQAd and BSA, with a partial disassembly of the nanoparticles in the presence of BSA and the formation of a complex between SQAd and BSA. The interaction free energy of SQAd nanoparticles with BSA derived from ITC experiments, is about −8 kcal mol −1 which is further supported in silico by ensemble docking simulations. Overall, our results show that serum albumin partially disassembles SQAd nanoparticles by extracting individual SQAd monomers from them. As a consequence, the SQAd nanoparticles would act as a circulating reservoir in the blood stream. The approach developed in this study could be extended to other soft organic nanoparticles.